Rapid Progression to Complete Paraplegia After Electroacupuncture in a Patient With Spinal Dural Arteriovenous Fistula: A Case Report - Park, Ki-Hoon; Jeon, Chang-Hoon; Chung, Nam-Su; Lee, Han-Dong (Frontiers in Surgery, 2021)
Spinal dural arteriovenous fistula (SDAVF) usually has an insidious clinical course, but 5–15% of cases have acute exacerbations. In some cases, there is abrupt progression to paraplegia following an epidural injection or anesthesia. Electroacupuncture is a form of acupuncture that applies a small electrical current to needles inserted at specific points in the body. It is widely used for its analgesic effect on back pain. Here, we report a rare case of SDAVF in which the patient’s symptoms worsened rapidly to complete paraplegia within a few hours after applying electroacupuncture to his back. A 49-year-old man had rapid progression to complete paraplegia within a few hours of electroacupuncture on his back. Magnetic resonance imaging showed SDAVF and worsening of cord signal change. An emergency operation was performed to ligate the SDAVF. The patient was able to walk 1 month postoperatively. Most of the neurological deficits had disappeared by 1 year postoperatively, with normalization of magnetic resonance imaging. Our case emphasizes that SDAVF patients should be careful when exposed to any circumstances that might affect the circulation around the dural arteriovenous fistula, such as electroacupuncture. Patients should also be warned in advance about the possibility of rapid exacerbation of neurological symptoms. Regardless of the severity of the neurological symptoms, immediate treatment is essential for recovery and a better outcome.